2018
DOI: 10.1249/mss.0000000000001566
|View full text |Cite
|
Sign up to set email alerts
|

Exercise Effects on Adipose Tissue Postprandial Lipolysis and Blood Flow in Children

Abstract: Daily bouts of acute aerobic exercise should be used to improve the antilipolytic and nutritive blood flow response to a subsequent meal in obese children.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 37 publications
0
2
0
Order By: Relevance
“…67 Clinical studies have shown that in adults with obesity, insulin poorly inhibits lipolysis, which may indicate that the hypertrophy of adipose tissue is resistant to insulin anti-lipolysis. 68 Clinically, it showed less insulin sensitivity in young adults with obesity accompanied by impaired glucose tolerance, including insufficient insulin action inhibiting lipolysis and lipid oxidation, as well as βcell dysfunction in lipid and glucose metabolism. 69 Wueest 70 showed that adipose tissue lipolysis mediated by glycoprotein 130 (gp130) promotes liver steatosis and insulin resistance.…”
Section: Anti-lipolysis Induced By Insulin In Adipose Hypertrophymentioning
confidence: 99%
“…67 Clinical studies have shown that in adults with obesity, insulin poorly inhibits lipolysis, which may indicate that the hypertrophy of adipose tissue is resistant to insulin anti-lipolysis. 68 Clinically, it showed less insulin sensitivity in young adults with obesity accompanied by impaired glucose tolerance, including insufficient insulin action inhibiting lipolysis and lipid oxidation, as well as βcell dysfunction in lipid and glucose metabolism. 69 Wueest 70 showed that adipose tissue lipolysis mediated by glycoprotein 130 (gp130) promotes liver steatosis and insulin resistance.…”
Section: Anti-lipolysis Induced By Insulin In Adipose Hypertrophymentioning
confidence: 99%
“…Biologically, arguments explaining why activity intensity may be relevant to obesity are speculative, including appetite regulation and insulin sensitivity improvement [ 27 ]. Evidence from an intervention study suggests that high-intensity physical activity as aerobic exercise can increase subcutaneous adipose nutritive blood flow and reduce suppression of lipolysis [ 28 ]. There is increasing emphasis that VPA can incite improvements in body composition and obesity.…”
Section: Discussionmentioning
confidence: 99%